How Do Housing Quality and Environmental Pollution Affect Older Adults’ Self-Rated Health? The Mediating Effect of Depression and Social Capital - Jinhui Song; Wen Zuo; Xuefang Zhuang; Rong Wu (Buildings, 2025)
With accelerated population aging, the importance of older adults’ self-rated health is constantly increasing. Self-rated health is influenced by complex relationships between the built environment and psychosocial factors. Therefore, this study constructs a pathway framework of “material (housing quality and environmental pollution)–psychological (depression and social capital)–self-rated health” elements to explore the influencing mechanism of older adults’ self-rated health. This study utilized the 2018 China Labor Force Dynamics Survey Database to explore the relationship between built environment factors (housing quality and environmental pollution), depression, social capital, and older adults’ self-rated health, using structural equation modeling. The heterogeneity between urban and rural areas is also analyzed. Better housing quality and less environmental pollution were found to be related to higher levels of self-rated health. Depression and social capital were important mediators in the relationship between housing quality, environmental pollution, and self-rated health. Regarding urban–rural heterogeneity, the direct impact of environmental pollution on self-rated health was only significant among urban older adults. Secondly, the multiple mediating roles of social capital were only reflected among rural older adults. The government and relevant entities should promote improvements in housing quality and reduce environmental pollution to achieve a healthy and livable environment.